Tax Competition and Profit Shifting: On the Relationship between Personal and Corporate Tax Rates - Clemens Fuest; Alfons Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 2002)
The residence-based taxation of interest income in the EU faces the difficulty that taxpayers may evade taxation by holding bank accounts in other countries. The EU therefore makes considerable efforts to achieve cooperation among EU member states in order to improve tax enforcement. The present paper argues that international cooperation in tax enforcement may not be sufficient to implement an effective taxation of interest income. The reason is that taxpayers may also avoid income taxes by holding financial assets in the corporate sector. If corporate tax competition reduces corporate income tax rates below personal income tax rates, taxpayers will increasingly shift income from the personal to the corporate sphere. We show that this type of income shifting is empirically important. According to our results, a one percentage point increase in the personal income tax rate increases the fraction of private savings held within corporations by approximately 2.6 percentage points.
Keywords: 330